PEMBUATAN WEBSITE SEBAGAI OPTIMALISASI PROMOSI PELAYANAN KLINIK PRATAMA BRASTOMOLO TEMANGGUNG: Making A Website As A Promotion Optimization Services at Pratama Clinic Brastomolo of Temanggung - MUKHAMAD MUSTA'IN (LPPM - STIKES Pemkab Jombang, 2020)
Abstract The development of technology is currently very supportive to be used as a means of promotion and information. Especially in the area of ??the website which is currently an information medium that offers various conveniences in presenting information. The website is more easily accessible to people in various regions by simply using the internet. One of them is in terms of marketing the products of a business, the website can be a means of promoting, marketing and conveying information effectively and efficiently to the public. Creating a website for marketing a product is needed, one of which is for the health sector. The Brastomolo clinic is no exception, which is involved in health services such as medical services, nursing services and pharmacies. The purpose of this activity is to increase staff knowledge about web development and introduce the Brastomolo clinic to the public through web media. The method used was conducting clinical web searches, then implementing training in making the clinic web development at Pratama Brastomolo. The result of this community service activity is the understanding of the staff in the good category (64%), sufficient knowledge (33%) and web development is still in the development stage. Thus it can be concluded that community service activities are running well and periodic monitoring of web development is required.